(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This study provides a concise overview of the sociological dimensions of gender inequality in the workplace, addressing historical roots, contemporary challenges, and the pivotal role of sociological analysis in understanding and mitigating this complex issue. Gender inequality in the workplace persists as a deeply entrenched societal phenomenon, reflecting historical norms and perpetuated by contemporary structures. This Study delves into the multifaceted nature of this challenge, emphasizing its implications for individuals, organizations, and society at large. Historically, gender roles have shaped expectations and opportunities in the workforce, leading to occupational segregation and unequal representation across industries. Despite strides towards gender equality, the gender pay gap remains a stark reminder of persistent disparities in remuneration, rooted in societal valuations of different types of work and discriminatory practices. The metaphorical "glass ceiling" encapsulates the invisible barriers impeding women’s progress into leadership roles, highlighting organizational structures and cultural norms that favor traditional masculine leadership qualities. Work-life balance, a crucial aspect of professional life, is intricately linked to gender inequality, often exacerbated by unequal domestic responsibilities. Sociologists contribute significantly to the understanding of gender inequality by employing various theoretical frameworks and historical analyses. By exploring global perspectives, societal expectations, and the impact of technology, sociological research sheds light on the intricate web of factors influencing workplace dynamics.